Access to Social Media, Knowledge, and Acceptance of COVID-19 Post-Vaccination Health Protocols: A Cross-Sectional Study - Armini, Ni Luh Gde; Lubis, Dinar Saurmauli; Widarini, Ni Putu (Kesmas, 2023)
The health protocols recommended by the health authorities still need to be practiced after having the COVID-19 vaccine. Education on the prevention of COVID-19 infection needs to continue to protect people from the disease. This study aimed to determine the factors associated with adhering to COVID-19post-vaccination health protocols in people aged 18 years and over in the South Denpasar Subdistrict. This cross-sectional study comprised a sample of 147 people who were selected by incidental sampling. The data were obtained using questionnaires from July to August 2022 and examined with bivariate and multivariate analysis. Most participants were female, private employees, went to senior high school, accessed social media, had high knowledge of COVID-19, and properly followed health protocols post-vaccination. However, only 34.7% of participants accepted the government’s policy for preventing COVID-19. Multivariate analysis showed that good social media access (aOR = 11.9; 95% CI = 3.6–39.8; p-value<0.001), high knowledge of COVID-19 infection (aOR= 2.6; 95% CI = 1.0–7.4; p-value = 0.044) and high acceptance of government policies (aOR = 4.1; 95% CI = 1.5–11.6; p-value = 0.006) were associated with the application of health protocols post-vaccination in people aged 18 years and over. In the studied group, having access to trusted social media, knowledge, and public acceptance of government policies led to adhering to the recommended health protocols post-vaccination.